Exploring the impact of a story-based teacher training programme on language and early literacy in 4- and 5-year-olds. Child characteristics, and teacher, classroom and home variables that predict improvements in language and literacy. - Cain, Kate; O'Carroll, Shelley; Oakhill, Jane; Klop, Daleen; Visser, Monique; Smith, Annelien; Swart, Anike (Wordworks, 2024)
This is the fifth in a series of five research briefs that explore the impact of a story-based teacher training programme on language and early literacy in 4- and 5-year-olds. This brief explores the impact of the intervention and the extent to which child characteristics, home learning environments, and teacher and classroom variables predict improvements in children’s language, literacy and overall development.
More information about the Little Stars training programme and materials can be found at: www.wordworks.org.za
Keywords: Early language; Early literacy; South Africa; Narrative; Vocabulary; isiXhosa; Afrikaans; ELOM; ECERS-E; Home learning environment; Teacher development